Supramolecular structural transformation of N, N′-bis(4-pyridylmethyl)-naphthalene diimide and fluorescence water sensing. (14th June 2017) - Li, Guo-Bi; Yang, Qing-Yuan; Pan, Rong-Kai; Liu, Shenggui; Xu, Yao-Wei
Abstract : The supramolecular organic structure exhibits reversible dehydration/rehydration in a single-crystal-to-single-crystal process, selective adsorption of CO2 over N2 as well as H2 and sorption selectivity for water and fluorescence sensing of water. Abstract : A supramolecular structure based on N, N ′-bis(4-pyridylmethyl)-naphthalene diimide exhibits reversible phase transitions in a single-crystal-to-single-crystal process. Such temperature induced SC–SC transformations are driven by intermolecular π–π interactions and hydrogen bond interaction. Interestingly, the dynamic supramolecular structure shows selective adsorption and fluorescence water sensing.